Composition and thermal properties of starch in flint maize (Zea mays, L.) kernels: location and crop management effects - Actis, Marcos; Farroni, Abel Eduardo; Andrade, Fernando Hector; Valentinuz, Oscar Rodolfo; Cirilo, Alfredo Gabriel (Gerencia de Comunicación e Imagen Institucional, DG-SICyP, INTA, 2020)
Flint maize kernels are processed by the dry-milling industry to produce the flaking grits used thereafter in the corn flakes industry. Flaking-grit yield during milling depends on kernel hardness whereas corn flakes production involves starch gelatinization. Starch composition influences both characteristics of maize kernels. The objective of this work was to analyze the effect of different crop environments and management practices on starch composition of kernels and its thermal properties. Two flint maize hybrids (Cóndor and Morgan, 306) were grown at three locations (Balcarce, Pergamino and Paraná, located in a latitudinal transect of 6°) with different plant densities (7.5 and 9 plants/m2 ), sowing dates (early and late), and fertilizing rates (with and without additional N and S-fertilizer near silking) during two growing seasons (2003-2004 and 2004-2005). Crop biomass accumulated from silking to physiological maturity was measured and mean kernel weigh was calculated at harvest. Kernel hardness was estimated by mean of the test weight and percent floaters. Amylose and starch concentration in kernels were determined. Starch thermal properties were analyzed by differential scanning calorimetry and endotherm parameters were calculated. Cropping conditions modified starch composition of kernels. Amylose/starch ratio decreased as air temperature decreased from the north to the south and by delaying sowing date. Deposition of amylose in the endosperm of the kernels increased as growing conditions for crop growth improved during kernel filling. Starch thermal properties were also modified by these changes in starch composition. The onset and peak temperatures, gelatinization enthalpy, and peak height index were positively associated with amylose concentration and amylose/starch ratio, whereas the gelatinization temperature range was negatively associated with both kernel attributes. The results reported herein would contribute to foresee the effect of location and agricultural practices on kernel quality of flint maize, and to make appropriated management adjustments to obtain a product that meets the market needs.